Effects of density ratio and diameter ratio on penetration of rotation projectile obliquely impacting a granular medium. Issue 4 (15th June 2015) - Ye, Xiaoyan; Wang, Dengming; Zheng, Xiaojing
Abstract : Purpose: – Granular material exhibits rich dynamical behaviors under impacting, and its impacting dynamical process is seriously influenced by many factors. The purpose of this paper is to explore the dynamical response of granular bed obliquely impacted by a rotational projectile, and the effect of density ratio and diameter ratio on its penetration depth is mainly considered. Design/methodology/approach: – In most experiments, as the angular velocity and the impact velocity always produce a coupling effect on the whole impact process, then it is quite difficult to separately distinguish the influence of angular velocity. Therefore, the discrete element method is used here to achieve this purpose. The authors vary one parameter and keep other parameter unchanged, and then discuss the effect of these parameters on penetration depth statistically. Findings: – The numerical model in this paper can effectively predict the dynamical process of granular medium under impacting. The projectile's penetration depth exhibits a similar scaling with its angular velocity under different density ratios and diameter ratios, and the angular velocity exhibits an obvious criticality. Originality/value: – A DEM code and corresponding statistical approach are used to explore the complex dynamical process of a granular material obliquely impacted by a rotation projectile.